2015
DOI: 10.1152/ajplung.00088.2015
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 isoforms bind directly exon B of the 5′-UTR of human surfactant protein A2 mRNA

Abstract: Human surfactant protein (SP) A (SP-A), an innate immunity molecule, is encoded by two genes, SFTPA1 and SFTPA2. The 5'-untranslated splice variant of SP-A2 (ABD), but not SP-A1 (AD), contains exon B (eB). eB is an enhancer for transcription and translation and contains cis-regulatory elements. Specific trans-acting factors, including 14-3-3, bind eB. The 14-3-3 protein family contains seven isoforms that have been found by mass spectrometry in eB electromobility shift assays (Noutsios et al. Am J Physiol Lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…6 ). Though the host miRNAs cannot target the YWHAZ pro-survival protein 76 , they can induce expression surfactant protein A2 77 , which might be indirectly modulated through viral protein NSP7 (Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Though the host miRNAs cannot target the YWHAZ pro-survival protein 76 , they can induce expression surfactant protein A2 77 , which might be indirectly modulated through viral protein NSP7 (Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein beta (YWHAB) was downregulated in the white pulp of spleen, heart and renal cortex of COVID-19 patients (SI Figure 8). It is a member of the 14-3-3 protein family, which mediates signal transduction by binding to phosphoserine protein and participates in metabolism, apoptosis and cell cycle regulation 191 .…”
Section: Stage 3: Proliferationmentioning
confidence: 99%
“…Several studies have identified differences between SP-A1 and SP-A2 in both qualitative (i.e., functional, biochemical, and/or structural) (45)(46)(47)(48), and quantitative (regulatory) functions (46,(49)(50)(51)(52)(53)(54)(55). In particular, these include surfactant secretion modulation (46), cytokine production (56)(57)(58), and phagocytosis by AM (47,48,59).…”
Section: Introductionmentioning
confidence: 99%